Real exchange rate persistence - Jusélius, Katarina,Assenmacher, Katrin (Swiss National Bank, 2015)
Asset prices tend to undergo wide swings around long-run equilibrium values, which can have detrimental effects on the real economy. To get a better understanding of how the financial sector and the real economy interact, this paper models the long swings in the Swiss franc-US dollar foreign currency market using the I(2) Cointegrated VAR model. The results show strong evidence of self-reinforcing feedback mechanisms in the Swiss-US foreign exchange market that are consistent with the observed pronounced persistence in Swiss-US parity conditions. Generally, the results provide support for models allowing expectations formation in financial markets to be based on imperfect information.
Parallel als Online-Ausg. erschienen
Keywords: Arbeitspapier; Graue Literatur; Devisenmarkt; Schweizer Franken; US-Dollar; Unvollkommene Information; Lange Wellen; Kointegration; VAR-Modell; Schweiz; USA; Long swings; Imperfect Knowledge; I(2) analysis; Selfreinforcing feed-back